Contactless parametric characterization of bandgap engineering in p-type FinFETs using spectral photon emission. (January 2019) - Beyreuther, A.; Vogt, I.; Herfurth, N.; Nakamura, T.; Fischer, G.G.; Motamedi, B.; Boit, C.
Abstract: In the last decade it has become increasingly popular to use germanium enriched silicon in modern field effect transistors (FET) due to the higher intrinsic mobility of both holes and electrons in SiGe as compared to Si. Whether used in the source/drain region (S/D) as compressive stressor, which is an efficient mobility booster on Si channel devices, or as channel material, the SiGe increases channel carrier mobility and thus enhancing device performance. Because the germanium content modifies the effective bandgap energy EG, this material characteristic is an important technology performance parameter. The bandgap energy can be determined in an LED-like operation of electronic devices, requiring forward biased p-n junctions. P-n junctions in FETs are source or drain to body diodes, usually grounded or reversely biased. This investigation applies a bias to the body that can trigger parasitic forward operation of the source/drain to body p-n junction in any FET. Spectral photon emission (SPE) is used here as a non-destructive method to characterize engineered bandgaps in operative transistor devices, while the device remains fully functional. Before applying the presented technique to a p-type FinFET device, it is put to the proof by verifying the nominal silicon bandgap on an (unstrained) 120 nm technology FET. Subsequently the characterization capability for bandgap engineering is then successfully demonstrated on a SiGe:C heterojunction bipolar transistor (HBT). In a final step, the bandgap energy EG of a 14/16 nm p-type FinFET was determined to be 0.84 eV, which corresponds to a Si0.7 Ge0.3 mixture. The presented characterization technique is a contactless fault isolation method that allows for quantitative local investigation of engineered bandgaps in p-type FinFETs.